Giant Depolarizing Potentials Trigger Transient Changes in the Intracellular Cl- Concentration in CA3 Pyramidal Neurons of the Immature Mouse Hippocampus - Lombardi, Aniello; Jedlicka, Peter; Luhmann, Heiko J.; Kilb, Werner (Frontiers in Cellular Neuroscience, 2018)
Giant depolarizing potentials (GDPs) represent a typical spontaneous activity pattern in the immature hippocampus. GDPs are mediated by GABAergic and glutamatergic synaptic inputs and their initiation requires an excitatory GABAergic action, which is typical for immature neurons due to their elevated intracellular Cl- concentration ([Cl-]i). However, since GABAA receptors are ligand-gated Cl- channels, activation of these receptors can potentially influence [Cl-]i. However, whether the GABAergic activity during GDPs influences [Cl-]i is unclear. To address this question we performed whole-cell and gramicidin-perforated patch-clamp recordings from visually identified CA3 pyramidal neurons in immature hippocampal slices of mice at postnatal days 4-7. These experiments revealed that the [Cl-]i of CA3 neurons displays a considerable heterogeneity, ranging from 13 to 70 mM (average 38.1 ± 3.2 mM, n=36). In accordance with this diverse [Cl-]i, GDPs induced either Cl--effluxes or Cl--influxes. In high [Cl-]i neurons with a negative Cl--driving force (DFCl) the [Cl-]i decreased after a GDP by 12.4 ± 3.4 mM (n=10), while in low [Cl-]i neurons with a positive DFCl [Cl-]i increased by 4.4 ± 0.9 mM (n=6). Inhibition of GDP activity by application of the AMPA receptor antagonist CNQX led to a [Cl-]i decrease to 24.7 ± 2.9 mM (n=8). We conclude from these results, that Cl--fluxes via GABAA receptors during GDPs induced substantial [Cl-]i changes and that this activity-dependent ionic plasticity in neuronal [Cl-]i contributes to the functional consequences of GABAergic responses, emphasizing the concept that [Cl-]i is a state- and compartment-dependent parameter of individual cells.